The departure from the strategy of the parent company from a developed economy by the business unit of a subsidiary in an emerging market in the professional services industry due to a change in the competitive environment caused by a downturn in the global economy - Price, Gavin (University of Pretoria, 2013)
Dissertation (MBA)--University of Pretoria, 2012.